PF-03882845, a non-steroidal mineralocorticoid receptor antagonist, prevents renal injury with reduced risk of hyperkalemia in an animal model of nephropathy - Orena, Stephen; Maurer, Tristan; Eudy, Rena; She, Li; Dash, Darla; Loria, Paula; Banker, Mary Ellen; Bernardo, Vincent; Tugnait, Meera; Okerberg, Carlin; Qian, Jessie; Boustany-Kari, Carine M. (Frontiers in Pharmacology, 2013)
The mineralocorticoid receptor (MR) antagonists PF-03882845 and eplerenone were evaluated for renal protection against aldosterone-mediated renal disease in uninephrectomized Sprague-Dawley (SD) rats maintained on a high salt diet and receiving aldosterone by osmotic mini-pump for 27 days. Serum K+ and the urinary albumin to creatinine ratio (UACR) were assessed following 14 and 27 days of treatment. Aldosterone induced renal fibrosis as evidenced by increases in UACR, collagen IV staining in kidney cortex, and expression of pro-fibrotic genes relative to sham-operated controls not receiving aldosterone. While both PF-03882845 and eplerenone elevated serum K+ levels with similar potencies, PF-03882845 was more potent than eplerenone in suppressing the rise in UACR. PF-03882845 prevented the increase in collagen IV staining at 5, 15 and 50 mg/kg BID while eplerenone was effective only at the highest dose tested (450 mg/kg BID). All doses of PF-03882845 suppressed aldosterone-induced increases in collagen IV, transforming growth factor-β 1 (Tgf-β 1), interleukin-6 (Il-6), intermolecular adhesion molecule-1 (Icam-1) and osteopontin gene expression in kidney while eplerenone was only effective at the highest dose. The therapeutic index (TI), calculated as the ratio of the EC50 for increasing serum K+ to the EC50 for UACR lowering, was 83.8 for PF-03882845 and 1.47 for eplerenone. Thus, the TI of PF-03882845 against hyperkalemia was 57-fold superior to that of eplerenone indicating that PF-03882845 may present significantly less risk for hyperkalemia compared to eplerenone.